2016
DOI: 10.1128/mcb.00976-15
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functions of the Eya Phosphotyrosine Phosphatase

Abstract: Eyes absent (Eya), a protein conserved from plants to humans and best characterized as a transcriptional coactivator, is also the prototype for a novel class of eukaryotic aspartyl protein tyrosine phosphatases. This minireview discusses recent breakthroughs in elucidating the substrates and cellular events regulated by Eya's tyrosine phosphatase function and highlights some of the complexities, new questions, and surprises that have emerged from efforts to understand how Eya's unusual multifunctionality influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 95 publications
0
25
0
Order By: Relevance
“…Expression of the Dachshund ( Dac ) gene is important for controlling cell fate determination in eye, limb, brain, and muscle development [38]. Drosophila eyes absent (Eya) plays an essential role in retinal cell survival and differentiation [39], while multiple functions of Eya homologues (Eya1, Eya2, Eya3, and Eya4) have been identified continuously in mammals [40]. These two genes, Dac and Eya , act synergistically to induce ectopic retinal development and positively regulate each other’s expression through conserved domains in Drosophila [41].…”
Section: Resultsmentioning
confidence: 99%
“…Expression of the Dachshund ( Dac ) gene is important for controlling cell fate determination in eye, limb, brain, and muscle development [38]. Drosophila eyes absent (Eya) plays an essential role in retinal cell survival and differentiation [39], while multiple functions of Eya homologues (Eya1, Eya2, Eya3, and Eya4) have been identified continuously in mammals [40]. These two genes, Dac and Eya , act synergistically to induce ectopic retinal development and positively regulate each other’s expression through conserved domains in Drosophila [41].…”
Section: Resultsmentioning
confidence: 99%
“…The ED domain is essential for mediating the interaction with other proteins, such as Six and Dach family proteins . The NTD domain contains a proline‐serine‐threonine‐rich region and functions as a transcriptional activator …”
Section: Introductionmentioning
confidence: 99%
“…5,6 The NTD domain contains a proline-serine-threonine-rich region and functions as a transcriptional activator. 7,8 Recently, accumulating evidence has shown that EYA functions in the mediation of DNA repair, cell apoptosis, angiogenesis and tumor growth. [9][10][11][12][13] EYA4 was found to be epigenetically silenced and was reported to function as a potential tumor suppressor gene in various types of common human cancers such as esophageal adenocarcinoma, 14 breast cancer, 15 lung cancer 16 as well as in oral dysplasia.…”
mentioning
confidence: 99%
“…While these interaction diagrams have been helpful in understanding the relationship amongst network members, they can be misleading since the network genes are expressed in dynamic patterns that change both spatially and temporally [18]. In addition, individual genes initiate expression at different times in development [6,8,9,11,17,19], are co-expressed with other network genes in some cells but not in others [18], and appear to interact differently depending upon the exact spatial, temporal, and developmental context [20,21]. As a result the static maps of regulatory interactions do not necessarily reflect the reality of what is happening throughout the eye in either space or time.…”
Section: Introductionmentioning
confidence: 99%